Data mining mobile devices - Mena, Jesus (Boca Raton : CRC Press, Taylor & Francis Group, 2013)
'Data Mining Mobile Devices, also known as'Reality Mining,' defines the collection of machine-sensed environmental data pertaining to human social behavior. This new paradigm of data mining makes possible the modeling of conversation context, proximity sensing, and temporospatial location throughout large communities of individuals. Mobile phones (and similarly innocuous devices) are used for data collection, opening behavior analysis to new methods of empirical stochastic modeling. The book explains how the combination of data mining and machine learning makes this possible, and details how to integrate the various technologies'--
Mobile sites -- Mobile apps -- Mobile data -- Mobile mobs -- Mobile analytics.
Includes bibliographical references and index.
Keywords: Data mining; Mobile computing; Web usage mining